Peran Artificial Intelligence dalam Meningkatkan Efisiensi dan Efektifitas Sistem Pendidikan - Juwika Afrita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Artificial Intelligence (AI) is an increasingly developing technology that plays an important role in various fields, including the education system. AI can enhance the efficiency and effectiveness of the education system through various methods, such as adaptive learning, predictive analytics, intelligent tutoring systems, natural language processing, and gamification. Artificial Intelligence (AI) is likely to continue to develop in the future. This is because AI has great potential to optimize and improve many aspects of human life, including in the fields of education, health, business, technology, and others. Therefore, researchers have taken this idea to optimize the function of AI in achieving efficiency and effectiveness in the education world. This research discusses the role of artificial intelligence in enhancing the efficiency and effectiveness of the education system. The literature review method was used to gather and analyze information related to this topic. The results of the research show that artificial intelligence can improve the efficiency and effectiveness of the education system by accelerating and facilitating the learning process, providing personalized recommendations, predicting student behavior, and improving data management.